The Effect of PHBS Education on Student Behavior in Maintaining the Cleanliness of the Primary School Environment - Handri Maika Saputra; Ayu Nurkhayati; Megawati; Suryani; Widyastuti Harianto (CV. Get Press Indonesia, 2025)
The implementation of Clean and Healthy Living Behavior (PHBS) in primary schools is a strategic step in shaping students’ character to care about cleanliness and environmental health. However, student behavior in maintaining school hygiene is often not optimal due to limited understanding and awareness of PHBS. Purpose: This study aims to determine the effect of PHBS education on student behavior in maintaining environmental cleanliness at SD Anduring, Padang. Method: A quantitative approach with a pre-experimental one-group pretest–posttest design was applied. The sample consisted of 50 students from grades IV and V selected purposively. Instruments used were validated questionnaires and observation sheets to measure changes in student behavior before and after education. The PHBS intervention was conducted through interactive counseling, including lectures, handwashing practice demonstrations, and audiovisual media, delivered in two sessions over two weeks. Results: Findings showed a significant improvement in hygiene behaviors such as proper waste disposal, classroom cleaning, and participation in environmental hygiene activities, with a significance value of p < 0.05. Implications: These results indicate that PHBS education is effective in increasing students’ awareness and responsibility toward the school environment and can be integrated into thematic learning and extracurricular activities. Conclusion: PHBS education has a positive and significant effect on student behavior in maintaining school cleanliness at SD Anduring Padang and is feasible to be developed as part of school culture.